Structured promotion of breastmilk expression is associated with shortened hospitalisation for very preterm infants. (June 2016) - Healy, David B.; Brennan, Ann‐Marie; O'Donovan, Rebecca; Daly, Veronica; Doolan, Anne; Dempsey, Eugene M.
Abstract: Aim: This study assessed neonatal outcomes following implementation of a structured, practical approach for promotion of breastmilk expression in mothers of very preterm infants. Methods: A multidisciplinary team developed a protocol that focussed on the enhancement of expression of human milk by mothers of very preterm infants. A pre‐ and poststudy intervention was subsequently performed. The group of infants enrolled in this time period was compared to a pre‐intervention group from 2010. Outcomes assessed included breastmilk expression, initiation of feeding, re‐attainment of birthweight, attainment of full enteral feeding, the incidence of necrotising enterocolitis (NEC), sepsis and duration of hospitalisation. Results: In total, 82 infants (39, 43) were included. While there was no statistically significant difference in earlier initiation of enteral feeding with EBM (median = 2 days) nor earlier achievement of fully enteral feeding (median = 12 days), birthweight was regained earlier in the postintervention cohort (mean = 10.42 days; p = 0.038) and there was a reduced length of stay (mean = 50 days; p = 0.021). Conclusion: A structured, focussed, multimodal approach to enhance breastmilk production has shown potential for producing positive end outcomes, particularly, a significant reduction in duration of hospitalisation.